Des allégories des Saisons sur les tissus coptes - Amandine Mérat (Les Cahiers de l'École du Louvre)
The identification of figures on Egyptian textiles of the Byzantine period (sixth-seventh centuries AD) is still a delicate and uncertain exercise due to the rarity of examples clearly named by inscriptions in Coptic or Greek. This search for identities is moreover often distorted or led astray by the Western vision of researchers who, influenced by Christian art of the medieval period, regularly attribute a Christian saintly dimension to any figure with a nimbus around his or her head. But during Late Antiquity, the nimbus was first and foremost an attribute of Roman and pagan origin, destined to highlight all sorts of illustrious figures, whether historical or mythological, such as emperors, heroes and allegories. Taking this observation as a starting point and based on examples from Greco-Roman art, itself strongly influenced by Egyptian weavers, an in-depth study of tapestries in the museums of the Louvre, Rennes and Rouen enabled the identification of the figures represented to be reconsidered and to demonstrate that they were in actual fact pagan allegories, linked to the theme of the Seasons.